2013
DOI: 10.3402/ejpt.v4i0.20274
|View full text |Cite
|
Sign up to set email alerts
|

Trauma histories among justice-involved youth: findings from the National Child Traumatic Stress Network

Abstract: BackgroundUp to 90% of justice-involved youth report exposure to some type of traumatic event. On average, 70% of youth meet criteria for a mental health disorder with approximately 30% of youth meeting criteria for post-traumatic stress disorder (PTSD). Justice-involved youth are also at risk for substance use and academic problems, and child welfare involvement. Yet, less is known about the details of their trauma histories, and associations among trauma details, mental health problems, and associated risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
289
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 389 publications
(322 citation statements)
references
References 36 publications
17
289
2
3
Order By: Relevance
“…This is in line with the literature that indicates a high prevalence of traumatic experiences, including shameful ones (Kerig & Becker, 2010), in both referred and forensic samples (Abram et al, 2004;Brigs et al, 2013;Dierkhising et al, 2013;Willis et al, 2013). Moreover, referred participants, as compared to community participants, reported more frequently having experienced shame, concurring with findings of a lower prevalence of trauma exposure in community samples of youth when compared to referred ones (Brigs et al, 2013).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This is in line with the literature that indicates a high prevalence of traumatic experiences, including shameful ones (Kerig & Becker, 2010), in both referred and forensic samples (Abram et al, 2004;Brigs et al, 2013;Dierkhising et al, 2013;Willis et al, 2013). Moreover, referred participants, as compared to community participants, reported more frequently having experienced shame, concurring with findings of a lower prevalence of trauma exposure in community samples of youth when compared to referred ones (Brigs et al, 2013).…”
Section: Discussionsupporting
confidence: 80%
“…This finding might be related to the fact that detained youth, though possessing a high prevalence of trauma exposure (Abram et al, 2004;Dierkhising et al, 2013;Willis et al, 2013), tend to deal with negative emotions by dissociation (Bennetti-McQuoid et al, 2015), denial (Ribeiro da Silva et al, 2015), or emotional numbing (Kerig & Becker, 2010;Kerig et al, 2012). This fact could difficult the assessment of shame and other negative emotions by self-report measures in this specific population.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Research on justice-involved youths has consistently found higher rates of adversity compared to youths in the general population, and they are more likely to have suffered multiple and chronic forms of trauma (Abram et al, 2004;Baglivio et al, 2014;Dierkhising et al, 2013). Furthermore, these youths have a greater likelihood of child protection involvement and foster care placements, exacerbating traumagenic factors that contribute to the development of delinquent behavior (Barrett, Katsiyannis, Zhang, & Zhang, 2013).…”
Section: The Frequency and Correlates Of Aces In Criminal Populationsmentioning
confidence: 99%
“…Events included a range of abuse and neglect, parental imprisonment, hospitalisations from As a comparison, juvenile detention studies in the USA have also found that significant numbers of adolescents (90%) experience high levels of trauma exposure. This compares to only a third of young people in the general population experiencing such events (Dierkhising, Ko, Woods-Jaeger, Briggs, Lee, & Pynoos, 2013). The recent Adverse Childhood Experiences (ACE) study identified that juvenile offenders (n = 64,329) experienced a range of adversity including sexual abuse, emotional abuse physical abuse and assault, neglect, family violence, substance use, and having a relative imprisoned (Baglivio et al, 2014).…”
Section: The Nature Of Trauma Exposure For Young Peoplementioning
confidence: 99%